If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-5x+11=-49
We move all terms to the left:
-5x+11-(-49)=0
We add all the numbers together, and all the variables
-5x+60=0
We move all terms containing x to the left, all other terms to the right
-5x=-60
x=-60/-5
x=+12
| (5x+2)²+15x+6=0 | | 8h^2-h=15 | | 16x-16=4{} | | 6t+6=5t-2 | | Ax-7=91 | | 6y-10+y=10/14 | | 2y-4×=40 | | 6y-10+y=10 | | (2 | | 0=86.010-(38-16)/100-70.041x(75/100)+36.76 | | 12x+x+12=78 | | |2x-3|=1.5 | | (2 | | (2 | | 33+4x=8-9x | | 3(×-5)+2(3x+1)=45 | | 2(3e–7)=5(6–e | | X+4.3x=6 | | 6-3(2x-4)=5(x-3) | | 2(4-3x/5)-9x=-7 | | -2q-7=-11 | | 21b+〖63b〗^2= | | (3^x)(2.718^7x+2)=15. | | 7x-18|=10 | | 7x-18|=10* | | -(6m+8)=4-m) | | 6(3x+4)^5=(18x+24)^5 | | 11x+2=-8 | | √5^n=625 | | 11.5/x=6 | | 2/3(3x+2)=3/4(3x-2) | | 8x-24=352 |